Death narratives and cervical cancer: Impact of character death on narrative processing and HPV vaccination - Krakow, Melinda; Yale, Robert N; Perez Torres, Debora; Christy, Katheryn; Jensen, Jakob D (Health psychology, 2017)
Narratives hold promise as an effective public health message strategy for health behavior change, yet research on what types of narratives are most persuasive is still in the formative stage. Narrative persuasion research has identified 2 promising features of such messages that could influence behavior: whether characters live or die, and whether characters encounter key barriers. This study investigated the effects of these 2 narrative message features on young women's HPV vaccination intentions and examined mediating psychological processes of narrative persuasion in the context of cervical cancer messages. We manipulated these 2 features in a narrative HPV vaccine intervention targeted to a national sample of U.S. women 18-26 who had not initiated the vaccine (N = 247). Participants were randomized in a 2 × 2 between-subjects experiment. Compared to death narratives, survival narratives increased narrative believability and self-efficacy while lowering perceived barriers to vaccination. As features interacted, survival narratives featuring social barriers led to greater narrative transportation (absorption into the story) than other combinations. Moderated mediation analysis tested 10 theoretically derived mediators; transportation and risk severity mediated the narrative-intention relationship. Findings provide evidence for key psychological postulates of narrative persuasion theory. Results inform practical application for the construction of effective narrative message content in cervical cancer prevention campaigns for young women. (PsycINFO Database Record